¿Cómo está organizado el estado peruano? Caso: conflictos políticos - Escudero Cabada , Andrés (2021)
Conflict can be seen in many ways, and the most common is to see it as the result of the social demands of the population. However, in its operation, the conflict is approached and led by political actors, who carry out strategies capable of affecting governance to force the Government to negotiate. Adopting the Heidelberg Barometer concept of “Political Conflict” this is characterized by actors avoiding formal or regular means of resolving their disputes using political means, including violence. When studying the Peruvian State, it has been possible to recognize that the greatest effort to face political conflicts and especially political violence is carried out by the Ministry of the Interior and especially the National Police of Peru. While the Presidency of the Council of Ministers and the other ministries have been organized to attend to social conflicts, without evaluating or developing strategies to confront those of political content.